COMPARISON ANALYSIS OF CONSUMER PERCEPTION BETWEEN I-PHONE 5S AND SAMSUNG GALAXY S5 - Akim, Lirvi Livana Wenas; Tielung, Maria (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The Development of business today has brought the business itself into a very tight competition to gain the attention of customers. Samsung and Apple are two companies that have very attractive products when compared with other brands in the industry. The purpose of this study is to compare the quality, value and company Reputation between i-Phone 5S and Samsung Galaxy S5 to know the difference of Consumer Perception of each product. This research is a comparison type. This research is a quantitative method since using questionnaire as a tool to gather data and analysis. The populations observed are young generation in Manado with sample 100 respondents. This research analyzes about the compare means with independent samples T-test between i-phone 5S and Samsung Galaxy S5 based on quality, value and company reputation. The result shows that are a mean different between i-phone 5S and Samsung Galaxy S5, and itâ€™s supported by level of significant. In terms of value and company reputation, consumers more interested of value and company consumers more interested of value and company reputation of i-Phone 5S. The management of smartphone company has to provide a good quality product, good value and good company reputation. Â  Keywords: quality, value, company reputation